Upper Trishuli-2 Hydroelectric Project - Dhungana, Santosh (Hydro Nepal: Journal of Water, Energy and Environment, 2016)
Not Available. HYDRO Nepal Journal Journal of Water, Energy and Environment Issue: 19 Page: 70